Cilostazol-based dual antiplatelet treatment in ischemic stroke or transient ischemic attack patients with asymptomatic carotid artery disease: a propensity score matching analysis - Thiraworawong, Thon; Pathonsmith, Chadawan (Frontiers in Neurology, 2024)
Background The optimal treatment for asymptomatic atherosclerotic carotid artery disease remains controversial. Data on the efficacy of antiplatelet agents and stroke outcomes are limited. This study aimed to examine the efficacy and safety of cilostazol-based dual antiplatelet therapy in patients with ischemic stroke or transient ischemic attack and asymptomatic carotid artery disease. Methods This retrospective cohort study was conducted in a tertiary-care setting and included baseline characteristics and clinical outcomes of participants. The study included patients who had experienced first-ever ischemic stroke or transient ischemic attack and asymptomatic atherosclerotic carotid artery stenosis, with a minimum follow-up period of 1 year. Asymptomatic carotid artery stenosis refers to stenosis in patients without neurological symptoms referable to the carotid arteries. Propensity scores were estimated using a logistic regression model based on participants’ baseline characteristics. The efficacy outcome was the composite outcome of recurrent ischemic events and vascular-related death in patients with ischemic stroke or transient ischemic attack and asymptomatic carotid artery stenosis. The safety outcome was the occurrence of hemorrhagic complications such as intracranial hemorrhages or extracranial hemorrhages. The effectiveness of dual therapy compared to monotherapy was evaluated at various time points following the initiation of antiplatelet treatment. Results This study included 516 patients with a 1-year follow-up period. At 1 year, composite events occurred in 10 (6.3%) patients in the dual antiplatelet group compared with 12 (7.6%) in the single antiplatelet group (HR, 0.74; 95% CI, 0.61–0.90; p = 0.024). Extracranial hemorrhage occurred in 12 (7.6%) patients in the dual antiplatelet group compared with nine (5.7%) in the single antiplatelet group (HR, 1.35; 95% CI, 1.13–1.48; p = 0.017). No intracranial hemorrhages were observed in this cohort. Conclusion Patients with asymptomatic carotid artery stenosis who received cilostazol-based dual antiplatelet therapy had a lower risk of composite events but a higher risk of minor extracranial hemorrhage than those who received a single antiplatelet agent.